2010
DOI: 10.1371/journal.pone.0008862
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Species Diagnosis for Invasive Candidiasis Using Mass Spectrometry

Abstract: BackgroundMatrix-assisted laser desorption ionisation time of flight mass spectrometry (MALDI TOF-MS) allows the identification of most bacteria and an increasing number of fungi. The potential for the highest clinical benefit of such methods would be in severe acute infections that require prompt treatment adapted to the infecting species. Our objective was to determine whether yeasts could be identified directly from a positive blood culture, avoiding the 1–3 days subculture step currently required before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 15 publications
3
62
0
2
Order By: Relevance
“…Several studies have been carried out on direct identification of yeasts from positive blood culture bottles using various protocols with varying results (Buchan et al, 2012;Drancourt, 2010;Ferreira et al, 2011;Idelevich et al, 2014;Lavergne et al, 2013;Marinach-Patrice et al, 2010;Yan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been carried out on direct identification of yeasts from positive blood culture bottles using various protocols with varying results (Buchan et al, 2012;Drancourt, 2010;Ferreira et al, 2011;Idelevich et al, 2014;Lavergne et al, 2013;Marinach-Patrice et al, 2010;Yan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have had very low success rates with fungi (Buchan et al, 2012;Idelevich et al, 2014), others have reported excellent levels of identification with different sample processing methods (Ferroni et al, 2010(Ferroni et al, , 2011Idelevich et al, 2014;Lavergne et al, 2013;Marinach-Patrice et al, 2010;Yan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies from Chen and colleagues 54 described automated capillary electrophoresis means to distinguish species of Candida according to the amplicon size, but later abandoned it due to lack of uniformity Recently, mass spectrometry using matrix assisted laser desorption/ionization-time of flight technology has been developed for microbiological identification and showed very promising results for rapid and reliable determination of the most important yeast species isolated in the clinical setting. [55][56][57] However, to date, mass spectrometry spectra of closely related species forming the major clinical Candida complexes and of unusual species have not been reported and have not been introduced into the reference databases. 56,57 Thus, additional inputs into the current databases using strains with unambiguous molecular-based delineation are required to allow accurate identification of these species for which, in particular, phenotypical methods are unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, an evaluation of specieslevel identification of Candida isolates from positive blood culture broth was reported. In their report, Marinach-Patrice et al [38] noted that a direct identification from the positive broth, bypassing subculture and subsequent identification steps, allowed re- …”
Section: ) Directly From Blood Culturesmentioning
confidence: 99%